З народної демонології закарпатців: нечистий (за експедиційними матеріалами) - Красиков, М. (Матеріали до української етнології, 2019)
Народна демонологія українців належить до пріоритетних тем сучасних дослідників народної культури. Ретельно вивчалася вона й етнографами та фольклористами ХІХ–ХХ століть. Не виключення – демонологія закарпатців. ЇЇ систематично вивчають сьогоднішні науковці, виїжджаючи в експедиції. За матеріалами, зібраними автором у фольклорно-етнографічній експедиції 2017 року по селах Рахівського району Закарпатської області, написана дана розвідка. The folk demonology of Ukrainians belongs to the priority subjects of the present-day researchers of folk culture. It has been studied assiduously also by the ethnographers and folklorists of the 19th – 20th centuries. Transcarpathians’ demonology is not an exclusion here. It is studied systematically by the scientists of today on expeditions. The proposed article is written after the materials, recorded by the author during the folklore-ethnographic expedition of 2017 in the villages of the Rakhiv district of the Transcarpathian region.